Effect of Fiber Length and Alkalization Treatment on the Tensile Properties of Musa Paradisia Banan Stick Fiber Composite - Gundara, Gugun; Refiadi, Gunawan; Lugiana, Yuda (International Journal of Integrative Sciences, 2024)
Composite materials are widely used and in demand in various applications, because they have advantages such as being light and relatively strong. The basic material used in this composite uses natural fiber because the fiber is environmentally friendly and is available in abundance in nature, making it more economical. The matrix as a binder uses epoxy. This research was conducted to determine the comparison of tensile strength of composites due to the influence of alkalisation and non-alkalization with a concentration of 5% NaOH for 2 hours with fiber lengths of 5 cm and 7 cm. The composite specimens made refer to the ASTM-D638 standard. The research method used four stages, namely taking kepok banana tree frond fibers, making composites, tensile testing and SEM testing. The highest tensile test results occurred in composites with alkalization treatment with a fiber length variation of 5 cm, namely 39.54 MPa. Meanwhile, the highest value for the composite without alkalization treatment occurred at a fiber length of 5 cm, namely 39.19 MPa. The highest elastic modulus value occurred in the composite with a 7 cm fiber variation of 4.76 GPa with alkalization treatment